Evaluating Clinical Implementation Approaches for Prostate Cancer Decision Support. Issue 2 (March 2019) - Berry, Donna L.; Hong, Fangxin; Halpenny, Barbara; Sanda, Martin G.; Master, Viraj A.; Filson, Christopher P.; Chang, Peter; Chien, Gary W.; Underhill, Meghan; Fox, Erica; McReynolds, Justin; Wolpin, Seth
Abstract: Introduction: Shared decision making is widely promoted for counseling men with localized prostate cancer. Results of randomized trials suggest decision aid efficacy. However, few practices or institutions have implemented decision support as standard practice. In this study we evaluated various implementation strategies for the decision aid P3P (Personal Patient Profile-Prostate) and analyzed feedback from clinical site staff and providers. Methods: A hybrid type 1 effectiveness-implementation trial was conducted. Primary data were collected in 6 urology clinics of 3 geographically distinct health networks. During the implementation phase site specific strategies were codesigned with site leaders. Referral and access metrics for men with localized prostate cancer were monitored for up to 7 months. Clinical staff reports of barriers and facilitators of implementation were evaluated in professionally facilitated focus groups. Results: Of 495 men with localized prostate cancer seen in the clinics 252 (51%, 95% CI 46-55) were informed of the program and of those men 107 (43%, 95% CI 36-49) accessed it. The highest access rates were observed with patient care coordinator e-mail and telephone contact (82%) or verbal physician instruction followed by e-mail and telephone invitations (87%). During focus groups physicians appraised the summaries as useful. Staff identified barriers included creating new workflows within heavy workloads, and staff misunderstanding of context and resources. Promoters of successful implementation included an identified clinical lead and physician engagement. Conclusions: Implementation success was realized when physicians engaged and staff provided followup contact. New practice changes to implement interventions require multimodal strategies for early success.